Clinical profile and prognostic indicators of tetanus in children - Kosam, Ajay; Kosam, Durga; Kumar, Hemant (International Journal of Medical Research and Review, 2015)
Introduction: Tetanus is still a major health problem in developing countries. There is paucity of published data regarding pediatric tetanus in study area. This study was conducted to describe the clinical profile, management outcome and prognostic indicators of tetanus in children in our region. Material and Methods: This was a 5 year retrospective study of 24 pediatric tetanus patients < 18 years of age (excluding neonatal tetanus) from January 2010 to December 2014 admitted in Pediatric Intensive care unit of Chhattisgarh Institute of Medical Sciences Bilaspur (C.G.). Mean, summation, percentage and frequency distribution were used where applicable. Results: A total of 24 cases were evaluated. The male to female ratio was 1.4: 1. The majority of patients (79.1%) were < 10 years of age. The mean age of cases were 6.94 ± 3.02 years (age range2 ½ - 12 years). Only 25% children with tetanus had prior tetanus immunization. Post injury tetanus (41.6%) and Otogenic tetanus (37.5%) were the most common mode of infection. The average incubation period and period of onset were 7.5 ± 3.13 days and 3.2 ± 0.96 days respectively. Complication rate was 54.1%. Mortality rate was 33.3%. Incubation period < 5 days, onset time < 3 days, presence of autonomic dysfunction, need for mechanical ventilation and severity of tetanus were associated with higher mortality. Conclusion: Otogenic tetanus is a common mode of infection in children. Emphasis should be given to maintenance of ear hygiene and appropriate tetanus immunization in children with chronic ear discharge.